Nanodrugs Targeting T Cells in Tumor Therapy - Haist, Maximilian; Mailänder, Volker; Bros, Matthias (Frontiers in Immunology, 2022)
In contrast to conventional anti-tumor agents, nano-carriers allow co-delivery of distinct drugs in a cell type-specific manner. So far, many nanodrug-based immunotherapeutic approaches aim to target and kill tumor cells directly or to address antigen presenting cells (APC) like dendritic cells (DC) in order to elicit tumor antigen-specific T cell responses. Regulatory T cells (Treg) constitute a major obstacle in tumor therapyby inducing a pro-tolerogenic state in APC and inhibiting T cell activation and T effector cell activity. This review aims to summarize nanodrug-based strategies that aim to address and reprogram Treg to overcome their immunomodulatory activity and to revert the exhaustive state of T effector cells. Further, we will also discuss nano-carrier-based approaches to introduce tumor antigen-specific chimeric antigen receptors (CAR) into T cells for CAR-T cell therapy which constitutes a complementary approach to DC-focused vaccination.